Exploration of mathematical concepts in determining good and bad days in the Mangbillang Allo tradition in the Enrekang community - Elma Gita Sukmara; Andi Aras (Ethnomathematics Journal, 2026)
This study aims to explore mathematical concepts contained in the Mangbillang Allo tradition in the Latimojong community, Enrekang. This tradition is a practice of determining good and bad days based on calculations rooted in local culture. The research focuses on identifying mathematical elements in the stages of the tradition, such as pentaunan (star observation), day and date calculations, and the wattu lima time system. The approach used is qualitative with an ethnographic method. Data collection techniques include observation, in-depth interviews with tradition practitioners, and documentation of calculation practices. Data analysis is conducted through domain and taxonomy approaches to identify mathematical concepts, which are then linked to six ethnomathematical activities according to Bishop: counting, measuring, locating, designing, and explaining. The research results indicate that the Mangbillang Allo tradition contains geometric concepts in the wattu lima symbol, arithmetic in number sequences and calculations of days based on the Hijri calendar, as well as patterns and modulo concepts. Its learning implementation includes four stages: informal, mode for mathematics, mode of mathematics, and formal. In addition, cultural values such as sipakatau, sipakalebbi, sipakario, and sipangingaran can be integrated into the learning process. These findings suggest that the Mangbillang Allo tradition has the potential as a context for mathematics learning that is contextual, meaningful, and based on local wisdom.